Aldosterone-stimulated endothelial epithelial sodium channel (EnNaC) plays a role in cold exposure–induced hypertension in rats - Tang, Liang-Liang; Yang, Xu; Yu, Shu-Qi; Qin, Qi; Xue, Rong; Sun, Yu; Xiao, Han; Shang, An-Qi; Liu, Jia-Qun; Han, Song-Qi; Liang, Chen; Lou, Jie; et al. (Frontiers in Pharmacology, 2022)
Abstract Background: Previous studies have demonstrated that activated endothelial epithelial sodium channel (EnNaC) impairs vasodilatation, which contributes to salt-sensitive hypertension. Here, we investigate whether mesenteric artery (MA) EnNaC is involved in cold exposure-induced hypertension (CIH) and identify the underlying mechanisms in SD rats. Methods: One group of rats was housed in room temperature served as control. Three groups of rats were kept in a 4°C cold incubator for 10 hours/day; among which two groups were administrated with either benzamil (EnNaC blocker) or eplerenone (mineralocorticoid receptor antagonist, MR). Blood pressure (BP), vasodilatation and endothelial function were measured with tail-cuff plethysmography, isometric myograph and total nitric oxide (NO) assay kit, respectively. Cell-attached patch-clamp technique, in split-open MA, was used to determine the role of EnNaC in CIH rat. Furthermore, the plasma aldosterone levels were detected using an ELISA kit and Western blot analysis was used to examine the relative expression levels of Sgk1 and Nedd4-2 proteins in the MA of SD rats. Results: We demonstrated that cold exposure increased BP, impaired vasodilatation and caused endothelial dysfunction in rats. The activity of endothelial EnNaC significantly increased, concomitant with an increased level of plasma aldosterone and activation of Sgk1/Nedd4-2 signaling. Importantly, CIH was inhibited by either eplerenone or benzamil. It appeared that cold-induced decrease in NO production and impairment of endothelium-dependent relaxation (EDR) were significantly ameliorated by either eplerenone or benzamil in MA of CIH rats. Moreover, treatment of MAs with aldosterone resulted in an activation of endothelial EnNaC, a reduction of NO and an impairment of EDR, which were significantly inhibited by either eplerenone, or GSK650394 (Sgk1 inhibitor) or benzamil. Conclusions: Activation of EnNaC contributes to CIH; we suggest that pharmacological inhibition of MR/Sgk1/Nedd4-2/EnNaC axis may be a potential therapeutic strategy for CIH.